COVID-19: A review of the effectiveness of non-pharmacological interventions - Odusanya, Olumuyiwa; Odugbemi, Babatunde; Odugbemi, Tinuola; Ajisegiri, Whenayon (The Nigerian postgraduate medical journal, 2020)
COVID-19, a highly infectious disease, caused by a novel virus, the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has brought about an unprecedented threat to global health. First reported in Wuhan, China, in December 2019, it has now spread to all continents of the world becoming a pandemic. There is no known treatment or vaccine for it although many candidate drugs and vaccines are in various clinical trial phases. For now, non-pharmacological interventions (NPIs) have become the mainstay of response for COVID-19 and are being used across the world to flatten the epidemiologic curve with some success. This review focussed on identifying which NPIs have been effective. NPIs that are effective include isolation and quarantine, physical distancing, use of face masks and hand hygiene. These measures are best used in combination and simultaneously. The evidence is that they should be instituted early in the pandemic and for sustained periods. They should also be implemented in the context of the cultural and socioeconomic conditions of the populace. Ineffective NPIs include ultraviolet irradiation and spraying of outdoor spaces and individuals. We recommend that decision makers weigh the evidence carefully, as it applies to the local setting to inform public health decisions.